Synergistic effect of nano-potassium and chitosan as stimulants inducing growth and yield of bird of paradise (Sterlitiza reginae L.) in newly lands - Eman A. Swedan; Kholoud Shible; Yassin M. Yassin; Aleksandra Glowacka; Mohamed A. A. Ahmed (Communicative & Integrative Biology)
The bird of paradise plant is a clumping tropical species native to South Africa. It is a dramatic plant with distinctive iridescent orange and midnight blue flowers that resemble an exotic bird peeking out from the broad leaves in autumn, winter and spring. An experiment was conducted during the two seasons of 2021 and 2022 at a private farm in Damanhour, Beheira Governorate, Egypt (31“°” 04 ”°“N, 30“°” 47’ °E) to study the effect different concentrations of nano-potassium and chitosan and their combinations on the bird of Paradise (Sterlitiza reginae). The experiment was conducted in a randomized complete block in a split-plot design with five replicates; nano-potassium was used at 0, 100, 150, and 200 mg/l and assigned to the main plots, whereas the sub-plots involved 0, 0.25, 0.50 and 0.75 g/l of chitosan. An increase in plant height and leaf length was recorded when the plants were treated with 200 mg/l nano-potassium and 0.75 g/l chitosan. Spraying plants with concentrations of 150 mg/l nano-potassium and 0.75 g/l chitosan is associated with the superiority of S. reginae plants in other traits, such as leaves wide, number of leaves/plant, days to flowering, number of inflorescence/plant, number of florets/inflorescence, stalk length and diameter, inflorescence weight, longevity of inflorescence, and flowering period, compared to the other treatments. We conclude that adding nano-potassium and/or chitosan to the bird of paradise plant leads to an improvement in terms of vegetative and yield characteristics under newly reclaimed lands.